The Application Of Slow Deep Breating Post Op Herniadectomy Patients With The Application Of Jean Watson's Theory At Muara Beliti Hospital, Musi Rawas Regency In 2022 - Rosdiana, Rosdiana; Murwati, Murwati; Sofais, Danur Azissah roeslina (Student Scientific Journal, 2023)
Intoduction: Hernia is a protrusion of the abdominal wall or from the abdominal cavity to other body cavities (hip or pelvis, chest or thorax) lined with protruding abdominal wall membranes (peritoneum), through weak parts of the abdominal wall that can contain intestines, intestinal hangers, or other abdominal organs, nursing problems that often arise in patients postoperative hernioraphy is acute pain associated with tissue discountuality due to surgery, Nutritional imbalances less than the body needs are associated with nausea and vomiting, impaired discomfort, risk of bleeding, and risk of infectionDeep breathing exercises or slow deep breating is one of the breathing relaxation techniques that can be done in people with hypertension. Slow deep breathing exercises consist of abdominal breathing (diaphragm) and purse lip breathingUsing the method is a nursing process approach based on the chosen nursing theory, the techniques used in data collection are interviews, observations, physical examinations and conducting nursing care. Data sources obtained or used are primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is studying source books related to nursing care given to patients.Slow deep breathing exercises can reduce lactic acid production in the muscles by increasing oxygen supply while oxygen demand in the brain decreases so that oxygen balance occurs in the oto. Deep and slow breathing stimulates autonomic nerves which has an effect on decreasing sympathetic nerve response and increasing body activity while sympathetic nerve response will increase body activity while parasympathetic nerve response tends to decrease body activity so that the body experiences relaxation and decreases metabolic activity.The goals of slow deep breathing exercises include maintaining gas exchange, improving alveoli ventilation, preventing pulmonary anteelectasis, helping to increase cough efficiency and reducing physical and psychological stress